Audible breath intakes in monologues - Mettouchi, Amina (Journal of Speech Sciences, 2019)
Although they have long been used in the transcription of spoken interactions, audible breath intakes have seldom been studied in their own right. This paper is a first step towards the analysis of their role and functions in a lesser-described language, Kabyle (Berber), in which oral storytelling is part of the traditional skills of older female speakers. Based on forty minutes (408 audible breath intakes) of monologue (two folktales and a personal recount), told by the same speaker, this perception- and acoustic-based study tests some hypotheses proposed in the literature concerning the correlation of breath intakes with disfluencies or sociolinguistic factors. It provides evidence for correlations between genre and audible breath intakes: while standalone audible breath intakes preceded by non-terminal boundary tones characterize the recount, the folktales are marked by a high number of complex pauses, preceded by terminal boundary tones, involving a silent pause preceding an audible breath intake. This qualitative study underlines the importance of segmenting various pause types, and annotating them.